THE IMPACT OF SERVICE ON 4-STAR HOTELS - Purwanti, Angel; Dimyati, Dindin (INSTITUT TEKNOLOGI DAN BISNIS INDOBARU NASIONAL, 2025)
Tourism is a key factor in income, job creation, business development, and infrastructure. Batam City, part of the Riau Islands province, lies along international shipping routes, making it a popular tourist destination in Indonesia. This research identifies the most impactful aspects of service and assesses the service factors. Using a descriptive quantitative approach. The researchers randomly took samples from customers of 4-star hotels in Batam City. The instrument used was a questionnaire containing questions about hotel services using a Likert scale. Interpretation uses the interpretation of results based on the average value and distribution of data to describe the impact of the most essential service factors and factors. The results of the study show that the 4-star hotel in Batam has had a positive effect, which means that customers are satisfied with the service provided by the hotel even though there are some minor improvements.